Atrial fibrillation virtual ward: reshaping the future of AF care. (3rd October 2022) - Kotb, A; Armstrong, S; Antoun, I; Koev, I; Mavilakandy, A; Barker, J; Vali, Z; Panchal, G; Li, X; Lazdam, M; Ibrahim, M; Sandilands, A; et al.
Abstract: Background: Atrial fibrillation (AF) hospital admissions represent significant AF related treatment costs nationally. In the year 2019–2020 our hospital reported 1, 333 admissions with a primary diagnosis of AF, with a 10% annual increase. A virtual ambulatory AF ward providing multidisciplinary care with remote hospital-level monitoring could reshape the future model of AF management. Methods: An AF virtual ward was implemented at our UK tertiary centre, as a proof-of-concept model of care. Patients admitted with a primary diagnosis of AF satisfying the AF virtual ward (AFVW) entry criteria (i.e., haemodynamically stable, HR <140 bpm with other acute conditions excluded) were given access to a single lead ECG recording device, a Bluetooth integrated blood pressure machine and pulse oximeter with instruction to record daily ECGs, blood pressure readings, oxygen saturations and fill an online AF symptom questionnaire via a smart phone or electronic tablet. Data were uploaded to an integrated digital platform for review by the clinical team who undertook twice daily virtual ward rounds. Medication adjustment was arranged through the hospital pharmacy. Data was collected prospectively for patients admitted to the AF virtual ward between 31 January and 11 March 2022. Outcomes included length of hospital stay, admission avoidance and re-admissions. Re-admission avoidance was assessed using the index admission criteria as a parameter for re-admission likelihood. Patients' satisfaction was assessed using the NHS family and friends' test (FFT). Results: Over the 6-week period a total of 14 patients were enrolled. One patient was unable to be onboarded because of technology related anxiety with 13 patients onboarded to the virtual ward, 30.7% (n=4) did not have smart phones and were provided with electronic tablets. The age on admission was 64±10 years (mean±SD) with the oldest at 78 years of age. All patients were in AF with a mean heart rate of 122±24 bpm, and 38.5% (n=5) were discharged from the virtual ward in sinus rhythm. One patient was onboarded directly from pacemaker clinic and hence hospital admission was completely avoided, and 5 re-admissions were avoided for 3 patients. One patient required brief readmission due to persistent tachycardia requiring acute cardioversion. The FFT yielded 100% positive responses among patients. Conclusion: This proof-of-concept is a first real world experience of a virtual ward for hospital patients with fast AF. It demonstrates a promising new telemedicine-based care model and with clear appetite among both patients and health professionals. This model of care has the potential to reduce the financial and backlog pressures caused by AF admissions without compromising patients' care or safety. Work is ongoing to further confirm the safety and cost-effectiveness upon further progress in a larger patient cohort. Funding Acknowledgement: Type of funding sources: None.